THE PLACE OF TERMS IN A LITERATURE TEXT - Turdiyeva Munisa Burxonovna (Modern American Journals, 2026)
This article explores the role and stylistic possibilities of terms in literary texts, their meaning in scientific discourse, their role as the basis for artistic and figurative expression, and their role as a linguopoetic tool.
Keywords: Term, word, artistic-aesthetic expression, artistic text, lexicon, artistic expressiveness.